PERANCANGAN COFFEE TABLE MODERN VINTAGE SEBAGAI SARANA KOMUNIKASI VISUAL METAMORFOSIS KUPU-KUPU GAJAH - Clarisa Isnaini Aulia Dewi; Nukhbah Sany (Universitas Negeri makassar, 2026)
The existence of designs, especially furniture design, exists as a creativity effort in order to fulfill the human activities necessities. In designing furniture, a designer faces a challenge to create something that is not only good in terms of construction, ergonomics, and function, but also in its aesthetics as well. In this research, the author designed and built a coffee table inspired by the elephant butterfly (Attacus atlas). Attacus atlas is now classified as an endangered species, therefore, the visualization of the metamorphosis of the specimen could act as an educational purpose towards its existence. The modern vintage theme was chosen in designing the coffee table, meanwhile the glass box method was used to support this article. The results were a design sketch of the coffee table and a prototype of the coffee table in 1:1 scale. In order to get objective feedback regarding the aesthetics aspect of the prototype, a questionnaire was given to 114 respondents. More than 70,5% respondent agreed that the prototype fulfilled aestethic’s aspects.